The Priority Needs of Secondary Schools Academic Management Based on The Concept of Entrepreneurial Leadership Competencies - Songkitipisal, Ittira; Chaemmchoy, Sukanya; Siribanpitak, Pruet (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
The purpose of this research aimed to study the priority needs of secondary school academic management based on the concept of entrepreneurial leadership competencies. This research adopted a quantitative approach. The sample was 345 secondary schools under the supervision of the Office of the Basic Education Commission, selected through multi-stage random sampling. There were 799 key respondents including administrators, course supervisors and teachers. The research adopted the questionnaire method as an instrument for collecting data. The data were analyzed by considering the frequency, percentage, means, standard deviation, and PNImodified for investigating the priority needs of secondary school academic management based on the concept of entrepreneurial leadership competencies. Regarding the secondary school academic management, the results showed that the highest priority needs index was the Measurement and Evaluation (PNImodified = 0.201), Curriculum Development (PNImodified= 0.200), and the Learning and Co-curriculum Activities Management (PNImodified = 0.168) respectively. By considering each aspect of the secondary school academic management, the highest priority needs of 1) the Curriculum Development aspect was the Task-oriented Competencies for Innovativeness, while the highest priority needs of 2) the Learning and Co-curriculum Activities Management, 3) the Measurement and Evaluation, and 4) the Media, Innovation, Technology, and Learning Resources Development was the Scenario Enactment Competencies for encouraging Risk-Taking in the learner.